2020
DOI: 10.2139/ssrn.3692541
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic-Related Emergency Psychiatric Presentations for Self-Harm of Children and Adolescents in 10 Countries (PREP-Kids): A Retrospective International Cohort Study

Abstract: To examine the differences in hospital emergency psychiatric presentations for self-harm of children and adolescents during the covid-19 lockdown in March and April 2020 compared with the same period in 2019. Retrospective cohort study. We used electronic patient records from 23 hospital emergency departments in ten countries grouped into 14 areas. We examined data on 2073 acute hospital presentations by 1795 unique children and adolescents through age 18. We examined the total number of emergency psychiatric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 19 publications
1
26
0
Order By: Relevance
“…Two studies, one of 16 EDs in British Columbia, Canada [ 8 ], and the other of a single center in the United States [ 9 ], reported significant decreases in mental health–related ED visits (41% and 60% decrease, respectively) during the first two months of the pandemic compared with the same period one year prior. Similarly, a retrospective study from 10 European countries found a significant decrease in the number of psychiatric emergency visits between March and April 2020 versus 2019 with a smaller proportion of youths admitted to an observation unit [ 10 ]. However, a small number of studies analyzing ED visits across the United States during the year 2020 showed a significant increase in the proportion of mental health–related visits among all adolescent visits in the second half of 2020 [ 11 , 12 ], with some studies reporting increases in the proportion of some (i.e., eating disorders, suicidality) but not all types of mental health visits [ 13 , 14 ].…”
mentioning
confidence: 99%
“…Two studies, one of 16 EDs in British Columbia, Canada [ 8 ], and the other of a single center in the United States [ 9 ], reported significant decreases in mental health–related ED visits (41% and 60% decrease, respectively) during the first two months of the pandemic compared with the same period one year prior. Similarly, a retrospective study from 10 European countries found a significant decrease in the number of psychiatric emergency visits between March and April 2020 versus 2019 with a smaller proportion of youths admitted to an observation unit [ 10 ]. However, a small number of studies analyzing ED visits across the United States during the year 2020 showed a significant increase in the proportion of mental health–related visits among all adolescent visits in the second half of 2020 [ 11 , 12 ], with some studies reporting increases in the proportion of some (i.e., eating disorders, suicidality) but not all types of mental health visits [ 13 , 14 ].…”
mentioning
confidence: 99%
“…3 An initial drop in presentations to paediatric emergency departments was also observed. 1 A similar picture has also emerged from the USA in young people from predominantly Hispanic/Latinx backgrounds where reductions in symptoms of mental health problems were found in the first month after COVID-19 restrictions were implemented. 4…”
Section: How Have Referrals To Camhs Changed?mentioning
confidence: 69%
“…Although the National Child Mortality Database indicated a possible increase in child suicide during the first UK lockdown, 15 self-harm presentations to emergency departments reduced very substantially at the beginning of the pandemic. 1 The impact of the pandemic on suicide remains unclear, but early studies show no substantial increase. 16 However, the longer-term impact of the pandemic and lockdown restrictions on this population remains unknown and we must remain vigilant in supporting these young people.…”
Section: Why Have Referrals To Camhs Changed?mentioning
confidence: 99%
See 1 more Smart Citation
“…Adolescents were found to represent a particularly vulnerable cohort [71]. Concomitantly, the clinical frontlines reported both a significant decline in the incidence of admissions for psychiatric emergencies during lockdowns [72][73][74] and increased suicide ideation and self-harm rates [75]. Such a rise in psychiatric emergencies overall, and specifically in suicide behaviours, is already documented in manifold reports and news article easily found through a Google search: we now await high-quality published studies empirically confirming this alarming trend beyond the grey literature, framing it developmentally as well as clinically.…”
Section: Introductionmentioning
confidence: 99%